Seismic Performance of Steel Column Base of Disc-spring Self-centering Energy-consuming Damper - SUN Jiateng; LIU Jianming; ZHU Guangzhi (工程科学与技术)
ObjectiveThe rapid restoration of the column base connection's functionality after an earthquake is crucial to the seismic performance of the structure. Currently, the existing self-centering column base connections have the drawbacks of complex construction, inability to integrate energy dissipation, self-resetting and replaceability. Proposes a new type of Disc-spring type self-centering energy dissipation steel column foot(DSSC-CF), a flexible column base connection that integrates self-resetting, replaceability and energy dissipation mechanisms. By relaxing the column base connection and limiting its rotation angle, it can rotate bidirectionally to achieve the goal of self-resetting for the structure's bidirectional seismic resistance function.MethodsFirstly, according to the seismic grade and the maximum load on the column foot calculated by the most unfavorable load combination, the flat load of the combined Disc-spring is determined, then the diameter and the number of combined discs are determined according to the size of the column foot, and then the stiffness of the combined Disc-spring is determined. The size of the shear energy dissipation plate is determined by using the principle of energy conservation, the size of the column foot and the size of the Disc-spring. Then, the finite element software ABAQUS is used to analyze the existing literature, and the existing experiments are modeled in ABAQUS, and their dimensions, material properties, contact properties between components, grid model properties and grid sensitivity analysis are defined, and the simulation results are compared with the experimental results, and the errors between them are analyzed to verify the effectiveness of the finite element model. Finally, abaqus is used to establish a new column foot joint and compare the simulation results of the traditional column foot joint. Then, based on the different number of shear energy dissipation plates, the pre-pressure value of Disc-spring device and the energy dissipation mild steel material, the influence of the three on the hysteretic performance, energy dissipation capacity and reset ability of the new column foot joint is obtained.Results and DiscussionsThe difference between the finite element simulation results and the existing literature test data is that the yield load error, peak load error and ultimate bearing capacity error of the simulated column foot joints are 6.9%, 8.4% and 12.6% respectively under forward loading. The corresponding errors in the process of reverse loading are 4.8%, 10.4% and 10.3%, and the errors are small. According to the finite element simulation results of the new type of column foot joint, the relative error between the simulated bearing capacity under positive loading and the theoretical calculation results is 2.53%, and the relative error under negative loading is 3.82%. In addition, according to the analysis of simulation results under six different working conditions, the maximum stiffness, maximum bearing capacity, maximum residual deformation and energy consumption are increased by 29%, 29.9%, 70.6% and 41.3% respectively when the pre-pressure of the Disc-spring device is increased. When the number of shear energy dissipation plates is increased, the maximum stiffness, maximum residual deformation and energy consumption are increased by 20%, 25% and 20% respectively. When the material strength of mild steel damper is reduced, the maximum stiffness decreases by 19.9%, the maximum residual deformation decreases by 12.5%, and the energy consumption decreases by 29.4%.ConclusionsThe results demonstrate the simulated hysteretic curve is in good agreement with the experimental hysteretic curve, and the set model parameters and modeling methods are effective. DSSC-CF can improve the bearing capacity and reduce the residual deformation by increasing the pre-pressure of the Disc-spring device. Increase the number of shear energy dissipation plates to improve the energy dissipation capacity of the structure; When the damper strength is reduced, the energy consumption is reduced, but the reset ability is improved.